How is students’ participation in a problem-solving project reflected in their drawings of a mathematics classroom? - Ebbelind, Andreas; Palmér, Hanna; van Bommel, Jorryt (LUMAT, 2024)
The mathematics teaching young students encounter not only affects the mathematics they are given the opportunity to learn but also their view of what mathematics is, how mathematics is taught and how they view their ability to learn mathematics. In this paper, an Educational Design Research study on problem solving and problem posing with Swedish six-year-olds will serve as an example. We elaborate on how students’ participation in education may affect their views of what it means to be taught and to learn mathematics. We do so by comparing drawings of mathematics classrooms made by students from eight classes, of which four attended the project. The results indicate a reform-oriented and more diverse view of content and form reflected in the drawings by the students participating in the intervention.